Overview of key performance indicators (Моделювання, керування та інформаційні технології, 2019)
A set of key performance indicators (KPIs) formanufacturing operation management is introduced in the ISO22400 standart. In this paper, a framework is introduced in orderto solve the problem of dividing into types all the 38 KPIs.